Nonlinear viscoelastic contact and deformation of freeform virtual surfaces. (16th February 2016) - Zafer, Naci; Yilmaz, Sezcan
Abstract: This article is concerned with the haptic deformation display of discrete viscoelastic surfaces by means of a human fingertip. The virtual surface of a deformable quadrilateral mesh is interactively deformed by a Kelvin–Voigt soft fingertip model attached to the end-effector of a haptic interface device. In achieving this task, a nonlinear constitutive model approximating experimental data from literature is developed for determining the contact point deformations. By employing a new kernel weighting function, the deformations are distributed dependently on the discrete surface topology based on a nonlinear spring–damper net around the contact location. For illustration and evaluation of the proposed approach, a parallel robotic device with a constraint-based controller is adopted. The grip of the device is moved by the user to feel a sense of touch as the soft fingertip deforms the mesh surface of an ex vivo porcine liver tissue. Experimental data indicates stable realistic interactions thorough mechanical coupling between the soft fingertip and the deforming liver tissue. Dynamic response data of liver show rate-dependent hysteretic deformations and match closely with experimental indentation data from literature. A thorough analysis of mesh node count on the sample rate and the rendering quality is also presented. Abstract :